Whose waves these are - Dykes, Amanda (Bethany House Publishers, 2019)
In the wake of WWII, a grieving fisherman submits a poem to a local newspaper: a rallying cry for hope, purpose . . . and rocks. Its message? Send me a rock for the person you lost, and I will build something life-giving. When the poem spreads farther than he ever intended, Robert Bliss's humble words change the tide of a nation. Boxes of rocks inundate the tiny, coastal Maine town, and he sets his calloused hands to work. Decades later, Annie Sawyer is summoned back to Ansel-by-the-Sea when she learns her Great-Uncle Robert, the man who became her refuge during the hardest summer of her youth, is now the one in need of help. But what greets her is a mystery: a wall of heavy boxes hiding in his home. Memories of stone ruins on a nearby island ignite a fire in her anthropologist soul to uncover answers. Together with the handsome and enigmatic postman, Annie uncovers the story layer by layer, yearning to resurrect the hope GrandBob once held so dear and to know the truth behind the chasm in her family's past. But mending what has been broken for so long may require more of her and those she loves than they are prepared to give.